Association Between Obesity Knowledge, Macronutrient Intake, and Nutritional Status Among Adolescents in Lamongan, Indonesia - Jakhyanur Indah Sugiarti; Annas Buanasita; Ani Intiyati; Nuning Marina Pengge (Journal of Nutrition Explorations, 2025)
Obesity is a global health epidemic that needs urgent attention and a health problem that must be addressed (World Health Organization). this study aims to analyze the relationship between obesity-related knowledge and dietary intake with the nutritional status of adolescents at SMA Pancamarga Lamongan. This quantitative study used a cross-sectional correlational design involving 47 students from SMA Pancamarga Lamongan, with data collected through interviews, food recalls, and anthropometric measurements, and analyzed using Spearman correlation. The results showed that the majority of respondents had a normal nutritional status (61.7%) and carbohydrate intake in the severely deficient category (51.1%). Spearman correlation analysis indicated no significant relationship between obesity-related knowledge (ρ = 0.111) or carbohydrate intake (ρ = 0.193) with the nutritional status of students at SMA Pancamarga Lamongan. The results showed that most respondents had normal nutritional status and severely inadequate carbohydrate intake, with no significant correlation found between obesity-related knowledge or carbohydrate intake and nutritional status.